62.9k views
4 votes
If f(x)=-5^x-4 and g(x)=-3x-2 find (f-g)(x)

2 Answers

5 votes

Answer:
(f-g)(x)=-5^x+3x-2.

Step-by-step explanation: We are given the following two functions :


f(x)=-5x^x-4,\\\\g(x)=-3x-2.

We are to find the expression for (f - g)(x).

We know that

for any two functions p(x) and q(x),


(p-q)(x)=p(x)-q(x).

So, we get


(f-g)(x)\\\\=f(x)-g(x)\\\\=(-5^x-4)-(-3x-2)\\\\=-5^x-4+3x+2\\\\=-5^x+3x-2.

Thus,
(f-g)(x)=-5^x+3x-2.

User Mosch
by
6.2k points
2 votes

Answer:


(f-g)(x) = 5^x +3x -2

Explanation:

The value (f-g)(x) means subtract the function g from f. This can be done by combining only like terms between each.


(f-g)(x) = 5^x - 4 -(-3x-2)\\(f-g)(x) = 5^x - 4 +3x + 2\\(f-g)(x) = 5^x +3x -2

User Actiwitty
by
6.1k points